2015
DOI: 10.1038/srep09083
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed rate of carcinogenesis and decreases in tumour volume and lung metastasis in CXCL14/BRAK transgenic mice

Abstract: Cancer progression involves carcinogenesis, an increase in tumour size, and metastasis. Here, we investigated the effect of overexpressed CXC chemokine ligand 14 (CXCL14) on these processes by using CXCL14/BRAK (CXCL14) transgenic (Tg) mice. The rate of AOM/DSS-induced colorectal carcinogenesis in these mice was significantly lower compared with that for isogenic wild type C57BL/6 (Wt) mice. When tumour cells were injected into these mice, the size of the tumours that developed and the number of metastatic nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 55 publications
1
41
1
Order By: Relevance
“…CXCL14 may also induce tumor suppression in other cancers beyond HPV-positive cancers, as CXCL14 expression is downregulated in several cancers including renal and gastric cancers [18,19]. Indeed, restoration of CXCL14 expression triggers tumor suppression in lung and colorectal cancers, as well as HNC [44,48,49]. In addition, CXCL14 could be used to treat HPV-positive premalignant lesions for cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL14 may also induce tumor suppression in other cancers beyond HPV-positive cancers, as CXCL14 expression is downregulated in several cancers including renal and gastric cancers [18,19]. Indeed, restoration of CXCL14 expression triggers tumor suppression in lung and colorectal cancers, as well as HNC [44,48,49]. In addition, CXCL14 could be used to treat HPV-positive premalignant lesions for cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of CXCL14 on cancer development remains controversial. Some reports have claimed antitumor and antiangiogenic effects of CXCL14 (47,48), whereas others noted upregulated expression of CXCL14 in several cancer types, including BrCa and osteosarcoma (49,50). A recent study also showed that CXCL14 expression in high stromal tissue, but not in epithelial tissue, is significantly associated with shorter survival in BrCa patients (51), raising the possibility that stromal CXCL14 may exert a procancer role in BrCa progression (52 vey the changes in 102 cytokines and chemokines in CM obtained from NAF10, CXCL14-activated NAF10, and CAF10 cells.…”
Section: Discussionmentioning
confidence: 99%
“…LLCm1 and LLCm1A cells were harvested with trypsin/ EDTA, resuspended in DMEM/F12 (pH 7.4) containing 10% FBS, and incubated at 37 °C for 1 h. The cells were washed twice with Mg 2+ and Ca 2+ -free phosphate-buffered saline (PBS(-)) and resuspended in ice cold PBS(-). In experimental metastasis assays [12,25,26], 3 × 10 5 cells in 200 µl PBS(-) were injected into the tail vein of each 7-week-old male C57BL/6 mouse (Clea Japan, Tokyo, Japan). Each experimental group consisting of 6 mice was housed in a cage.…”
Section: Lung Metastasismentioning
confidence: 99%